2004
DOI: 10.1021/jo048263p
|View full text |Cite
|
Sign up to set email alerts
|

Self-Aggregation of Synthetic Zinc Oxo-Bacteriochlorins Bearing Substituents Characteristic of Chlorosomal Chlorophylls

Abstract: We prepared novel zinc 8-ethyl-8-methyl-7-oxo- and 7-ethyl-7-methyl-8-oxo-bacteriochlorins 1 and 2 possessing substituents characteristic of chlorosomal chlorophylls, exclusively observed in extramembraneous light-harvesting antennas of photosynthetic green bacteria. The electronic absorption spectra of monomeric 1 and 2 in THF were obviously different: the Q(y) maximum of the former was 724 and that of the latter was 683 nm. This observed spectral difference was clearly explained by theoretical ZINDO/S calcul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Moreover, chlorosome-like self-aggregation of synthetic porphyrins possessing three chlorosomal moieties has also been reported, [36,45] where the 13-formyl-(or keto)-carbonyl group in synthetic zinc 3 1 -hydroxyporphyrin acts as a chlorosomal substituent without the E-ring, thus suggesting that conformationally free 13-COR (R = H, CH 3 ) is also acceptable for the formation of such selfaggregates. Furthermore, our FT-IR experiments have indicated that the zinc chlorins 1-3 self-aggregate using only the 13-methoxycarbonyl group, in a similar manner to natural BChl-e (7-CHO) [18] and previously reported (bacterio)chlorins, [42,46,47] where an additional C=O moiety at the 7-, 8-, or 13 2 -position is excluded from the hydrogen-bonding network. Thus, the 13-COOCH 3 group in the zinc chlorins 1-3 is sufficient to induce chlorosomal self-aggregation.…”
Section: Oligomeric States Of Zinc Chlorins 1-3: the 13-methoxycarbonsupporting
confidence: 80%
See 3 more Smart Citations
“…Moreover, chlorosome-like self-aggregation of synthetic porphyrins possessing three chlorosomal moieties has also been reported, [36,45] where the 13-formyl-(or keto)-carbonyl group in synthetic zinc 3 1 -hydroxyporphyrin acts as a chlorosomal substituent without the E-ring, thus suggesting that conformationally free 13-COR (R = H, CH 3 ) is also acceptable for the formation of such selfaggregates. Furthermore, our FT-IR experiments have indicated that the zinc chlorins 1-3 self-aggregate using only the 13-methoxycarbonyl group, in a similar manner to natural BChl-e (7-CHO) [18] and previously reported (bacterio)chlorins, [42,46,47] where an additional C=O moiety at the 7-, 8-, or 13 2 -position is excluded from the hydrogen-bonding network. Thus, the 13-COOCH 3 group in the zinc chlorins 1-3 is sufficient to induce chlorosomal self-aggregation.…”
Section: Oligomeric States Of Zinc Chlorins 1-3: the 13-methoxycarbonsupporting
confidence: 80%
“…Since most of the synthetic models prepared mimic the molecular structure of natural BChls by possessing the E-ring, their absorption and emission properties are similar to natural BChls. The self-aggregated porphyrin [23,48] and bacteriochlorin molecules [23,42,49] reported previously have their oligomeric Qy maxima at shorter (640-650 nm) and longer wavelength regions (780-880 nm), respectively, compared with the typical chlorin self-aggregates. These variations are accomplished by modifying the π-conjugated systems of the composite molecules.…”
Section: Oligomeric States Of Zinc Chlorins 1-3: Absorption and Emissmentioning
confidence: 99%
See 2 more Smart Citations
“…The way in which bacteriochlorophyll (BChl) molecules self-assemble to form the light-harvesting complexes found in the chlorosomes of green sulfur bacteria, however, remains a subject of debate in the absence of Xray crystallographic evidence. In particular, Tamiaki and coworkers [8,[84][85][86][87] and Balaban et al [7,[88][89][90] have put much effort in devising (semi-)synthetic mimics of self-assembling BChl units to investigate the self-assembling structures. Balaban recently made a very convincing case for a model, in which BChl monomers are assumed to selfassemble through intermolecular interactions between the central magnesium atom of one BChl molecule, the ketone oxygen atom of one of its BChl neighbors, and the hydroxy oxygen atom of the other neighbor (Figure 14, right).…”
Section: Relevance To Biological Systemsmentioning
confidence: 99%